MODERN MECHANISMS OF INVOLVING YOUNG PEOPLE IN THE DEVELOPMENT OF CIVIL SOCIETY - Kostieva, Tetiana (Public Administration and Regional Development, 2021)
The article considers the most promising areas of youth involvement in the process of formation of civil society, taking into account the importance of deploying the European integration strategy in Ukraine. The special role of the study of social Internet networks and the need to form a system of civic education as the leading tasks of ensuring the real participation of young people in the development of domestic civil society is substantiated. It is emphasized that young people are now the leading creators of the global “network society, the most powerful system-forming resource of which are social Internet networks, which perform several important social functions, including serving public interests and needs and forming public opinion. It is proved that Ukrainian youth can become an influential actor in civil society by overcoming imitation initiatives and practices of civic activity, forming a sense of political responsibility at the individual and group levels as a basis for establishing a "mature" civil society.